THEORETICAL AND METHODOLOGICAL BASIS OF THE APPLICATION OF SMART SERVICES IN INCREASING THE ECONOMIC EFFICIENCY OF CONSTRUCTION ENTERPRISES - Kurbanova Maftuna Lazizovna (Modern American Journals, 2025)
The purpose of this article is to highlight the main benefits of implementing intelligent services in construction companies. Among them, such technologies as digital twin, BIM (building information modeling), construction robots and autonomous vehicles are analyzed. Intelligent services also contribute to increasing the transparency of construction processes and enhancing interaction between all project participants. Thanks to sensors, real-time monitoring systems and cloud platforms, data is collected in one place, accelerating and increasing the accuracy of decision-making. This is of great importance for reducing unexpected risks, improving the quality of work and ensuring strict compliance with safety measures. Overall, the article discusses how intelligent services can not only simplify the construction process, but also lead the entire industry ecosystem to a more innovative and sustainable future.
Keywords: Construction, intelligent services, digital twin, BIM technologies, artificial intelligence, 3D printing, intelligent construction technologies.